Anxiety and depression among adolescent students at higher secondary school - Bhandari, M (BIBECHANA, 2016)
This study was conducted to assess the association of depression and anxiety with selected variables; low academic performance and poor parent adolescent relationship among the adolescent students at Arniko Higher Secondary school at Biratnagar. Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) tools were used for data collection. Spearman’s Rank Correlation Coefficient and Chi Square test were applied to assess the significant variables. The findings of the study revealed that there was significant correlation between total depression and total anxiety score i.e. Spearman’s rank correlation coefficient value was 0.554 (p = 0.000). The study also found that the depression and anxiety were significantly associated with type of family (p =0.005 & p = 0.015). The depression was significantly associated with academic performance of adolescent students (p = 0.030) and major accident in the family (p =0.009). Similarly, the anxiety was significantly associated with parental fight (p = 0.007), conflict with father (p = 0.019), and death of family member (p = 0.016). It can be concluded that adolescent anxiety and depression are significant mental health problems so further studies are needed to validate the findings. BIBECHANA 14 (2014) 103-109